The Role of Collaboration and Integration in the Supply Chain of Construction Industry - Fazal Ali Shaikh; Muhammad Saeed Shahbaz; Saad Ud Din; Nasurullah Odhano (Salehan Institute of Higher Education, 2020)
It has found that the construction sector of Pakistan is growing fast due to the China-Pakistan Economic Corridor but history shows that construction projects never achieves its targets. The literature revealed the major hurdles behind the construction is supply chain issues. Supply chain of construction is deficient due to lack of collaboration and integration. The aim of this study is the empirically verify the role of supply chain collaboration (information sharing, Joint decision making, and risk and reward sharing) and supply chain integration (supplier integration, internal integration, and customer integration) with performance. This is a quantitative study, a total of 350 questionnaires were distributed to registered construction firms with Pakistan Engineering Council and 221 were received and considered for analysis after purification, validity and reliability. Multiple-regression technique was applied through SPSS. This study has unique findings as all integration approaches have significant effects while collaboration is not working for the same industry. This proves that members of supply chain construction can get benefit from integration but they hesitate to share their risks, rewards, and planning to all stakeholders. This study will help managers in decision making. This study will also help the government of Pakistan and China in completing their construction projects in time and with the designated cost.